Does transcription by RNA polymerase play a direct role in the initiation of replication? - Hassan, A; Cook, P (1994)
RNA polymerases have been implicated in the initiation of replication in bacteria. The conflicting evidence for a role in initiation in eukaryotes is reviewed.